2021
DOI: 10.3390/su13179949
|View full text |Cite
|
Sign up to set email alerts
|

Population Flow Mechanism Study of Beijing-Tianjin-Hebei Urban Agglomeration from Industrial Space Supply Perspective

Abstract: The growing demographic dividend is declining worldwide due to global population shrinkage. However, with the enhancement of spatial connection, industry-oriented population flow is becoming more and more active. The floating demographic dividend will bring new opportunities to regional development. Population flow has become an important field of urban research. We selected the Beijing-Tianjin-Hebei urban agglomeration as the study area and conducted the study of the interaction relationship between populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, the facts obtained from the field showed that most local communities tend to develop store ventures and informal activities at the housing location developed due to farmland conversion and natural environmental destruction. Therefore, all efforts to restore the biological habitats and compensate the harmed citizens further mitigated the spill's effects and may have resulted in improvements of some community amenities in the affected areas [42].…”
Section: A Socio-economic Characteristics Of New City Regionmentioning
confidence: 99%
“…Furthermore, the facts obtained from the field showed that most local communities tend to develop store ventures and informal activities at the housing location developed due to farmland conversion and natural environmental destruction. Therefore, all efforts to restore the biological habitats and compensate the harmed citizens further mitigated the spill's effects and may have resulted in improvements of some community amenities in the affected areas [42].…”
Section: A Socio-economic Characteristics Of New City Regionmentioning
confidence: 99%
“…The topics on population flow in China have drawn numerous interests, but studies have mainly analysed within a region rather than the entire country (Y. Chen et al, 2021;F. Wang, Wei, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Flow analysis takes a different perspective and may provide new findings because the attraction of a destination towards different origins is no longer treated as homogeneous. The topics on population flow in China have drawn numerous interests, but studies have mainly analysed within a region rather than the entire country (Y. Chen et al, 2021; F. Wang, Wei, et al, 2019). Network analysis methods have been utilized in such studies because population flow can be considered a weighted two‐way network for population exchange between regions, and adding the flows at every node yields the distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transportation infrastructure in addition to providing ease of movement and accessibility also has an impact on population mobility, circular migration, and increased traffic volume. This means that transportation activities contribute to water, air, and soil pollution [44]. Thus, transportation system connectivity, in addition to contributing to the integration of urban systems, also contributes to environmental degradation.…”
Section: Fig 3 Changes In Land Use In the New City Area Of The Moncongloe-pattalassangmentioning
confidence: 99%